Innovation in Islamic Education in the Digital 4.0 Era in Learning Media Al Qur'an at High School Khadijah Surabaya - Abdul Hamid Mahmud; Abdul Haris; Masdar Hilmy (International Journal of Integrative Sciences, 2023)
Learning the Bil Qolam Method Online at the Khadijah High School Education Institution which includes planning, implementation, evaluation, the strategy of the Khadijah Surabaya High School Institution in facilitating the needs of supporting students' online learning, Inhibiting and supporting factors in the learning process. This research is a qualitative descriptive study, with research subjects covering the principal, Ustad supervisor, and students who take part in the online bil qolam program, totaling 54 students. Data collection techniques used are observation, interviews, and documentation. The learning carried out at the Khadijah High School Surabaya Educational Institution is by way of an oral evaluation which is done through direct observation of the clerics during the online learning process. The evaluation is carried out in three stages, namely daily evaluation, weekly evaluation, and semester evaluation. The implementation of the evaluation is adjusted to the needs of the students. The results showed that: 1) Learning the bil qolam method online includes planning, implementation and evaluation. 2) Strategy of School Education Institutions in improving students' learning outcomes of recitation of the Qur'an. 3) obstacles in the application of the bil qolam method online arise when students feel bored with this learning method, to eliminate this boredom sometimes ustad makes a kind of quiz to increase students' enthusiasm for learning, implementation and evaluation